Molecular markers for analyses of genetic diversity within the Anastrepha fraterculus complex with emphasis on Argentine populations - Gomulski, Ludvik; Vera, María Teresa; Lanzavecchia, Silvia Beatriz; Piccinno, Riccardo; Fiorenza, Giulia; De Luca, Daniel; Carrizo, Beatriz Noemi; Bouvet, Juan Pedro; Viana, Valeria Angelica; Cárceres, Carlos; Enkerlin, Walther; Malacrida, Anna; et al. (MDPI, 2025)
The South American fruit fly Anastrepha fraterculus (Wiedmann) has a vast range extending from northern Mexico, through Central America, to South America where it is an extremely polyphagous pest of wild and cultivated fruits. It is a complex of cryptic species currently composed of eight recognised morphotypes: “Mexican”, “Venezuelan”, “Andean”, “Peruvian”, “Ecuadorian”, and the three Brazilian morphotypes “Brazilian-1”, “Brazilian-2”, and “Brazilian-3”. Molecular markers that can identify the member species of the complex are crucial for the implementation of effective pest control measures, such as the sterile insect technique. The object of this study was to evaluate the use of the internal transcribed spacer 2 (ITS2) sequence for discriminating several members of the A. fraterculus cryptic species complex (Mexican, Peruvian, and Brazilian-1) and a related species, Anastrepha schultzi Blanchard. The analysis highlighted significant genetic differentiation between the evaluated morphotypes, allowed their discrimination within the A. fraterculus cryptic species complex, and provided new insights into their genetic relationships. The ITS2 marker provides a basis for the development of taxonomic keys for the discrimination of the cryptic taxa within the A. fraterculus cryptic species complex. ITS2 also represents an important marker for the poorly studied species A. schultzi.